2021
DOI: 10.1155/2021/8847472
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Anemia among Pregnant Women of Underprivileged Ethnic Groups Attending Antenatal Care at Provincial Level Hospital of Province 2, Nepal

Abstract: Background. This study aims at determining the factors associated with anemia among pregnant women of underprivileged ethnic groups attending antenatal care at the provincial level hospital of Province 2. Methods. A hospital-based cross-sectional study was carried out in Janakpur Provincial Hospital of Province 2, Southern Nepal. 287 pregnant women from underprivileged ethnic groups attending antenatal care were selected and interviewed. Face-to-face interviews using a structured questionnaire were undertaken.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 29 publications
4
14
1
1
Order By: Relevance
“…Observed also was that pregnant teenagers who had had antenatal care attendance of less than four were more than 8 fold likely to be anemic than the teenagers who had attended more than four times. This nding was consistent with results in studies carried out by Jusoh et al, (7) in Malaysia, Yadav et al, (21) in Nepal, and Anlaakuu and Anto (22) in Ghana, as all these studies showed that pregnant teenagers with less than four antenatal care clinic visits had higher chances of having anemia than those four visits or more. Certain antenatal care packages such as early trimester screening for hemoglobin status and appropriate intervention for those detected with anemia, health education of every pregnant woman about anemia in pregnancy, its complications and prevention, timely initiation on iron and folate supplements, deworming to prevent hookworm infestation, and intermittent presumptive treatment for malaria are all key components of Uganda's antenatal care package and these are all known to have a serious preventive impact on anemia in pregnancy.…”
Section: Discussionsupporting
confidence: 93%
“…Observed also was that pregnant teenagers who had had antenatal care attendance of less than four were more than 8 fold likely to be anemic than the teenagers who had attended more than four times. This nding was consistent with results in studies carried out by Jusoh et al, (7) in Malaysia, Yadav et al, (21) in Nepal, and Anlaakuu and Anto (22) in Ghana, as all these studies showed that pregnant teenagers with less than four antenatal care clinic visits had higher chances of having anemia than those four visits or more. Certain antenatal care packages such as early trimester screening for hemoglobin status and appropriate intervention for those detected with anemia, health education of every pregnant woman about anemia in pregnancy, its complications and prevention, timely initiation on iron and folate supplements, deworming to prevent hookworm infestation, and intermittent presumptive treatment for malaria are all key components of Uganda's antenatal care package and these are all known to have a serious preventive impact on anemia in pregnancy.…”
Section: Discussionsupporting
confidence: 93%
“…This study identified that women of economic, ethnic, geographic disadvantage, and linguistic minorities (e.g., Maithili speaking women) received poor quality MNH services. These women also have low levels of power and poor social positioning in Nepalese society [ 84 , 85 ] compared to women from advantaged ethnic groups, who usually also have wealth status. These latter groups are usually Nepali native speakers with good access to education, employment, and health information, compared to disadvantaged ethnicities who belong to the lower strata in the hierarchical caste system of Nepal [ 86 ].…”
Section: Discussionmentioning
confidence: 99%
“…When HIV infection is observed among those who have not attended formal education, the risk of poor nutrition and the occurrence of anaemia will be double burdened. Additionally, non-educated patients are not fully aware of anaemia symptoms, so they will come to the hospital quite late with high anaemic grades 31 32…”
Section: Discussionmentioning
confidence: 99%